Pengaruh Kondisi Keuangan Perusahaan, Debt Default, Dan Opini Audit Tahun Sebelumnya Terhadap Penerimaan Opini Audit Going Concern (Studi Kasus Pada Perusahaan Sektor Aneka Industri Yang Tercatat Di Bursa Efek Indonesia Tahun 2015 - 2019) - Irawati Sardi; Silvi Reni Cusyana; Amrizal Amrizal (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
The influence of Financial Condition, Debt Defualt, and Audit Opinions of Prior Year of the acceptance of Going Concern Opinios in the miscellaneous sectors listed at Indonesia Stock Exchange in the year 2015 - 2019. South Tangerang. Under the guidance of Mrs. Silvi Reni Cusyana S.E., M.Ak. This study aims to examine the influence of financial condition, debt default, and audit opinions prior year in the miscellaneous sectors of the acceptance going concern opinion. This study using secondary data sources with two data collection techniques, using financial document and literature review. The result of this study regarding financial condition has a significant ef ect to acceptance of going concern audit opinions. Debt default and audit opinions of prior year do not have significant ef ect to acceptance of going concern audit opinions in miscellaneous sectors listed at Indonesia stock exchange in the year 2015 - 2019